Biochar addition reduces non‐CO2 greenhouse gas emissions during composting of human excreta and cattle manure - Castro‐Herrera, Daniela; Prost, Katharina; Kim, Dong‐Gill; Yimer, Fantaw; Tadesse, Menfese; Gebrehiwot, Mersha; Brüggemann, Nicolas (Journal of environmental quality, 2023)
Ecological sanitation combined with thermophilic composting is a viable option to transform human excreta into a stabilized, pathogen‐free, and nutrient‐rich fertilizer. In combination with suitable bulking materials such as sawdust and straw, and additives such as biochar, this could also be a suitable waste management strategy for reducing greenhouse gas (GHG) emissions. In this study, we conducted a 143‐days thermophilic composting of human excreta or cattle manure together with teff straw, organic waste, and biochar to investigate the effect that biochar has on GHG (CO2, N2O, and CH4) and NH3 emissions. The composting was performed in wooden boxes (1.5 × 1.5 × 1.4 m3), GHG were measured by using a portable FTIR gas analyzer and NH3 was sampled as ammonium in an H2SO4 trap. We found that the addition of biochar significantly reduced CH4 emissions by 91% in the cattle manure compost, and N2O emissions by 56%−57% in both humanure and cattle manure composts. Overall, non‐CO2 GHG emissions were reduced by 51%−71%. In contrast, we did not observe a significant biochar effect on CO2 and NH3 emissions. Previous data already showed that it is possible to sanitize human fecal material when using this composting method. Our results suggest that thermophilic composting with biochar addition is a safe and cost‐effective waste management practice for producing a nutrient‐rich fertilizer from human excreta, while reducing GHG emissions at the same time. Core Ideas Composting of human and cattle manure with biochar reduced N2O emission up to 57%. Composting of cattle manure with biochar reduced CH4 emission up to 91%. Biochar addition to compost did not significantly affect CO2 and NH3 emissions. Overall, non‐CO2‐GHG emissions were reduced by 51%−71% by biochar addition.